1993
DOI: 10.1111/j.1530-0277.1993.tb00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Ingestion Increases Susceptibility of Mice to Listeria monocytogenes

Abstract: Excessive consumption of alcohol is associated with an increase in the frequency and severity of infectious diseases. Ethanol adversely affects specific and nonspecific aspects of the immune response. We used a murine model to determine whether ethanol ingestion impairs host mechanisms of resistance to Listeria monocytogenes. Naive mice and mice immune to L. monocytogenes were pair-fed either a Leiber-DeCarli liquid diet containing 7% (v/v) ethanol or an isocaloric control diet for 7 days. Then, nonimmune mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
53
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
7
53
1
Order By: Relevance
“…It has been important, therefore, to develop suitable animal models in order to provide key insights into the extent to which the detrimental effects on resistance mechanisms are caused only by ethanol. For example, an alcohol-related decrease of protection has been reported to occur in response to viral infection (4) and to listerial infection in mice (24) and during salmonellosis in mice (25). Consistent with these findings are earlier reports of members of our group 1996) showing that after rats were fed intoxicating amounts of ethanol, they developed significant hematologic and immunologic changes, including decreased humoral and cellular immune responses to bacterial antigens.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…It has been important, therefore, to develop suitable animal models in order to provide key insights into the extent to which the detrimental effects on resistance mechanisms are caused only by ethanol. For example, an alcohol-related decrease of protection has been reported to occur in response to viral infection (4) and to listerial infection in mice (24) and during salmonellosis in mice (25). Consistent with these findings are earlier reports of members of our group 1996) showing that after rats were fed intoxicating amounts of ethanol, they developed significant hematologic and immunologic changes, including decreased humoral and cellular immune responses to bacterial antigens.…”
supporting
confidence: 80%
“…Listeriosis is not as severe a disease in rats as it is in mice. The 50% lethal dose (LD 50 ) in mice (13,24) is about a thousandfold less than the amount of Listeria (5 ϫ 10 7 CFU) that was used here to infect our rats, yet all of our test rats survived, including a few that were observed for an additional 2 to 3 weeks after challenge. This would seem to suggest that we might be using an avirulent strain of Listeria.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the immunosuppressive effects of acute alcohol use have been linked to alterations in NF-B activation (1)(2)(3). Previous data suggested that universal inhibition of NF-B binding by alcohol via various receptor systems occurs independent of IB␣ degradation (24).…”
Section: Acute Alcohol Consumption Inhibits Lps-induced Nf-b Binding mentioning
confidence: 99%
“…The complexes are held in the cytoplasm and prevented from activation by a class of proteins referred to as inhibitors of NF-B or IB proteins. Upon stimulation, the IB proteins are phosphorylated by the IB kinases (IKK) 3 IKK␣, IKK␤, and IKK␥, ubiquitinated, and degraded thereby releasing the NF-B complex for nuclear translocation (11). Recent studies have shown that in addition to this canonical NF-B activation, NF-B proteins are modified posttranslationally, and these changes can influence transcriptional activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation